2019
DOI: 10.12659/msm.912737
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Adiponectin Gene rs1501299 Polymorphism and Nonalcoholic Fatty Liver Disease Susceptibility: A Systematic Review and Meta-Analysis

Abstract: BackgroundMetabolic related nonalcoholic fatty liver disease (NAFLD) is one of the most prevalent chronic liver diseases around the world. A single nucleotide polymorphism (SNP) rs1501299 (+276G>T) in the adiponectin gene has been recently revealed to be responsible for susceptibility to NAFLD. This meta-analysis intended to assess the association risk of NAFLD and rs1501299 polymorphism.Material/MethodsWe conducted a literature search on PubMed, Embase, and Cochrane Library databases. All involved studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Regarding carbohydrate metabolism disorders in NAFLD, our data are the same as those obtained in recent studies [17]. The data of our study confirm the influence of the G276T polymorphism of the ADIPOQ gene on biochemical parameters in patients with NAFLD and AH [10,14,15].…”
Section: Table 3 Comparative Evaluation Of Metabolic Parameters Of Patients With Comorbidity Of Nafld and Rpah In G/g And G/t + T/t Genotsupporting
confidence: 91%
“…Regarding carbohydrate metabolism disorders in NAFLD, our data are the same as those obtained in recent studies [17]. The data of our study confirm the influence of the G276T polymorphism of the ADIPOQ gene on biochemical parameters in patients with NAFLD and AH [10,14,15].…”
Section: Table 3 Comparative Evaluation Of Metabolic Parameters Of Patients With Comorbidity Of Nafld and Rpah In G/g And G/t + T/t Genotsupporting
confidence: 91%
“…Many data literature described the association between APM1 polymorphisms and increased incidence and susceptibility to metabolic disorders, but these data are still ambiguous. Nevertheless, several data have been produced about the effects of SNPs (single-nucleotide polymorphisms) in the APM1 gene on Adiponectin serum concentrations (Zandoná et al, 2013;Liu et al, 2019). The resulting protein is a 244 amino acid open reading frame containing 4 domains, a short N-terminal region, a hypervariable region with no homology to any known protein domain (secretory signal sequence of 66 amino acids), a collagen-like domain (Gly-X-Y repeats), and a C-terminal globular domain that presents a high homology to C1q (Kadowaki et al, 2006;Shehzad et al, 2012).…”
Section: Adiponectin: Structural Characteristicsmentioning
confidence: 99%
“…In rat models 107 , 108 as well as in human subjects with NAFLD, 51 , 109 , 110 the concentration of adiponectin was significantly decreased and adiponectin gene polymorphisms associated with NAFLD were found. 111 , 112 One publication investigated the association between serum retinol-binding protein 4 (RBP4) and NAFLD. 113 In this study, they found lower RBP4 levels in patients with NASH than in patients with simple steatosis.…”
Section: Potential Biomarkers Of Novel Liver Fat Indicesmentioning
confidence: 99%